Vital role for Plasmodium berghei Kinesin8B in axoneme assembly during male gamete formation and mosquito transmission. (12th December 2019) - Depoix, Delphine; Marques, Sara Rute; Ferguson, David JP; Chaouch, Soraya; Duguet, Thomas; Sinden, Robert E; Grellier, Philippe; Kohl, Linda
Abstract: Sexual development is an essential phase in the Plasmodium life cycle, where male gametogenesis is an unusual and extraordinarily rapid process. It produces 8 haploid motile microgametes, from a microgametocyte within 15 minutes. Its unique achievement lies in linking the assembly of 8 axonemes in the cytoplasm to the three rounds of intranuclear genome replication, forming motile microgametes, which are expelled in a process called exflagellation. Surprisingly little is known about the actors involved in these processes. We are interested in kinesins, molecular motors that could play potential roles in male gametogenesis. We have undertaken a functional characterization in Plasmodium berghei of kinesin‐8B (PbKIN8B) expressed specifically in male gametocytes and gametes. By generating Pbkin8B‐gfp parasites, we show that PbKIN8B is specifically expressed during male gametogenesis and is associated with the axoneme. We created a ΔPbkin8B knockout cell line and analysed the consequences of the absence of PbKIN8B on male gametogenesis. We show that the ability to produce sexually differentiated gametocytes is not affected in ΔPbkin8B parasites and that the 3 rounds of genome replication occur normally. Nevertheless, the development to free motile microgametes is halted and the life cycle is interrupted in vivo . Ultrastructural analysis revealed that intranuclear mitoses are unaffected whereas cytoplasmic microtubules, although assembled in doublets and elongated, fail to assemble in the normal axonemal '9+2' structure and become motile. Absence of a functional axoneme prevented microgamete assembly and release from the microgametocyte, severely reducing infection of the mosquito vector. This is the first functional study of a kinesin involved in male gametogenesis. These results reveal a previously unknown role for PbKIN8B in male gametogenesis, providing new insights into Plasmodium flagellar formation.